ANALISIS YURIDIS TERHADAP HAK UJI MATERIIL PUTUSAN MAHKAMAH AGUNG NOMOR 68 P/HUM/2014 TENTANG PUNGUTAN OLEH OTORITAS JASA KEUANGAN ATAS KEWAJIBAN PUNGUTAN PROFESI NOTARIS PASAR MODAL - NOVIA GRACIA TOBING (PREMISE LAW JURNAL, 2017)
The philosophical bases of OJK fee from the profession of capital market support are the 1945 Constitution, and Article 34 of Law No. 3/2004 on Bank Indonesia as the basis for the birth of Law No. 21/2011 on OJK in which Article 37, paragraph 6 indicates the provision on fee regulated in PP No. 11/2014 on OJK Fee from those who perform their activity in financial service sector. The positive effect of OJK fee is that it will be used for administrative activity, the procurement of assets and other supporting activities which can be used by industry (recycling), and for professions in financial service sectors. Its negative effect is that it will decrease the trust of professionals in professional associations like Notarial Profession, INI. If the fee is not paid, sanction in fine and administration will be imposed. Judge’s legal consideration is that OJK fee is not contrary to the 1945 Constitution and to the other legal provisions; therefore, the request for judicial reviews is not reasonable because it is not in accordance with Law No. 21/20011 on OJK. Keywords: Fee, Financial Service Authority, Notary, Supporting Profession, Capital Market